STRATEGI ADAPTASI SOSIAL MAHASISWA PAPUA PENERIMA BEASISWA AFIRMASI DIKTI (ADik) DI UNIVERSITAS RIAU - Saputra, Candra; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Riau University, the purpose of this research is to know and analyze The Strategy Social Adaptation of Papua Students Recipients of Scholarship Afirmasi Dikti in Riau University. This research is Qualitative research which analyzed descriptively, and instrument of data is observation and interview. The theory used in this research is Bourdieuw theory. In this study of informants there are eight people. Sampling technique is Snowball Sampling the result of the research on the informants explained that the students of papua who studied at the university Riau able to adapt to the campus environment by learning to accept and follow the rules, approach to friends and also lecturers, and their friends always help when they have trouble in following lesson, and their friends always helpful when experiencing difficulties in terms of communicating, so that papua students are able to adapt in Riau UniversityKeywords : Strategy,Adaptation, Papua Students.